Always contemporary messages of Archibald Reiss - Rastović, Aleksandar (Sociološki pregled, 2025)
We will review a recently published monograph R. A. Reiss: Neutrality is not possible in the face of crime by Uroš Šuvaković, which was published on the occasion of the 110th anniversary of Archibald Reiss’s arrival in Serbia, and 95 years since his death. Although Reiss’s scientific and professional contribution is considered to have been largely explored and that it primarily belongs to the domains of forensics and criminology, as well as historical science in relation to testimonies about crimes committed against Serbs during the First World War, Šuvaković’s approach is original because he points to sociological dimensions of Reiss’s research which have neither been observed in scientific public nor adequately valorized, and that is exactly the value of this book.
Keywords: Rudoph Archibald Reiss; Yugoslav society; interwar period; research; sociological aspect